Investigating the parameters influencing Islamic banks financial performance: evidence from five Southeast Asian countries - Fahd Al-Shaghdari, Fahd Al-Shaghdari; Tahani Ali Hakami, Tahani Ali Hakami; Barjoyai Bardai, Barjoyai Bardai; Saleh, Abdulmajid Obaid Hasan (Springer, Cham, 2023)
View expanded cover International Conference on Business and Technology